Стратегічні напрями розвитку міжнародного туризму - Демко, Валентина Сергіївна; Demko, Valentyna (Запоріжжя : 2024, 2024)
UA: Стаття присвячена стратегічним напрямкам розвитку міжнародного туризму. Виявлено ключові фактори, які впливають на туристичну діяльність та визначено успішні стратегії для їх впровадження. Визначено стратегічні напрями, глобальні чинники, що впливають на розвиток міжнародного туризму, сформовано переваги сталого туризму. Розроблено та запропоновано рекомендації та практичні кейси щодо реалізації стратегій розвитку у сфері міжнародного туризму з урахуванням специфіки галузі та потреб ринку. EN: Abstract. The article is devoted to the strategic directions of international tourism development. The relevance of the topic lies in the need to research and develop effective strategies and approaches to improving tourism development. The purpose of the study is to determine the strategic directions that determine the further development of the tourism sector at the global level. Results. The study identifies the strategic guidelines for the development of world tourism, identifies the key economic aspects and benefits of sustainable tourism development that affect the strategies for the development of international tourism. Recommendations and practical cases on the implementation of development strategies in the field of international tourism, taking into account the specifics of the industry and market needs, are developed and proposed. Conclusions. Prospects for the development of international tourism at the global level are determined by a number of factors, including growing interest in travel, development of transport infrastructure, changing consumer preferences, technological progress, and changing economic conditions. Key areas for the industry's development may include the growth of tourism in environmentally friendly regions, the development of digital technologies, an increase in the number of international tourism events and festivals, the growth of medical and health tourism, and exotic tourism, and the development of tourism in rural regions.
Strategic directions for the development of international tourism
Keywords: сталий туризм; туристична сфера; туристичний потік; міжнародний туризм; стратегічний розвиток; міжнародне туристичне співробітництво; sustainable tourism; tourism sector; tourist flow; international tourism; strategic development; international tourism cooperation